quanto que é 2(x-1)-3(2x-5)=6x-3
Soluções para a tarefa
Respondido por
0
2(x-1)-3(2x-5)=6x-3
2x-2-6x-15=6x-3
2x-6x-6x=-3+2+15
-10x=20 (-1)
10x= -20
x= -20/10
x= -2
mariafernandatpeesoh:
se eu não me engano hehe :3
Respondido por
0
Cálculo acima. Espero ter ajudado.
Anexos:
![](https://pt-static.z-dn.net/files/dff/3eaf5767422c1f29c4b49ffa1dd5538a.jpg)
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Biologia,
10 meses atrás
Geografia,
1 ano atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás